2007
DOI: 10.1051/forest:2006100
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and divergence among Italian populations of common ash (Fraxinus excelsior L.)

Abstract: -The level of genetic variation throughout the Italian range of common ash (Fraxinus excelsior L.) was estimated using six microsatellite markers. High levels of allelic diversity was detected. The levels of expected heterozygosity for each of the populations ranged from 0.726 to 0.871, with an average of 0.798, and indicated that populations have a high level of genetic variation. A general and significant homozygote excess was found at most loci in all populations, with an overall mean F IS of 0.284. Possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 42 publications
3
24
2
2
Order By: Relevance
“…Chestnut pollination is mainly entomophilous (Manino et al, 1991;Oliveira et al, 2001), and this species has large, sticky pollen, which may reduce gene flow among populations due to poor ability of pollen to be moved by wind (Ferrazzini et al, 2007). We thus suggest that the presumed low gene flow may lead to reduced genetic variation within populations.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Chestnut pollination is mainly entomophilous (Manino et al, 1991;Oliveira et al, 2001), and this species has large, sticky pollen, which may reduce gene flow among populations due to poor ability of pollen to be moved by wind (Ferrazzini et al, 2007). We thus suggest that the presumed low gene flow may lead to reduced genetic variation within populations.…”
Section: Discussionmentioning
confidence: 87%
“…In the Iberian peninsula, considered by several authors as a possible site of its autochthonous origin (Aira-Rodríguez and Ramil-Rego, 1995;Fineschi et al, 2000;García-Antón et al, 1990;Krebs et al, 2004), it is present as a natural or naturalised tree. The scattered distribution and isolation of populations may have resulted in differentiation among chestnut populations in adaptive traits (Ferrazzini et al, 2007), with drought and frosts being expected to be causal forces of natural selection (Fernández-López et al, 2005a). In fact, several authors have observed differentiation among populations for different adaptive traits, such as vigour, growth initiation and cessation, and drought resistance (Fernández-López et al, 2005a;2005b;Lauteri et al, 2004;Pliura and Eriksson, 2002), and some of these authors have suggested drought as a selective force in natural selection.…”
Section: Introductionmentioning
confidence: 99%
“…At least for the case of the widespread common ash in Europe, genetic diversity results derived from nuclear microsatellite loci Ferrazzini et al, 2007;Gerard et al, 2006;Hebel et al, 2006;Heuertz et al, 2001;Morand et al, 2002) suggest that allelic richness and gene diversity are fairly similar. Yet, more important than the numbers of alleles is the identity of those alleles and genetic conservation should favor the preservation of private alleles (Kalinowski, 2004;2005), a result only possible if several populations are sampled.…”
Section: Discussionmentioning
confidence: 99%
“…The phylogeography of the species is now well described (Morand et al, 2002;Heuertz et al, 2004;Ferrazzini et al, 2007). F. excelsior displays a complex, polygamous sexual system (FRAXIGEN, 2005) in which individuals may be classified phenotypically across a continuum from purely male to purely female with a whole range of hermaphroditic intermediates.…”
Section: Methodsmentioning
confidence: 99%